Single-walled carbon nanotubes as a photo-thermo-acoustic cancer theranostic agent: theory and proof of the concept experiment - L. Golubewa (Nature Portfolio, 2020)
Abstract Theranostics is the emerging field of medicine that uniquely combines diagnostic techniques and active agents to diagnose and treat medical conditions simultaneously or sequentially. Finding a theranostic agent capable to cure the affected cells and being safe for the healthy ones is the key for successful treatment. Here, we demonstrate that agglomerated single-walled carbon nanotubes (SWCNTs) are promising theranostic agent that enables photo-activated ‘cold’ destruction of the cancer cells keeping their environment alive. The absorption of picosecond pulses by SWCNT agglomerates results in the mechanical (due to photoacoustic effect) rather than photothermal cancer cell destruction, which was visualized by micro-Raman and ultrafast near-infrared CARS. The developed theoretical model allows us to distinguish photothermal, photoacoustic, and photothermoacoustic regimes of the cancer cell destruction, and also to optimize SWCNT-based theranostics recipe.